PENGUATAN NIAT BERWIRAUSAHA: PEMBERIAN PENDIDIKAN KEWIRAUSAHAAN DAN EFIKASI DIRI MAHASISWA - Euis Siti Rohayati; Edi Fitriana Afriza (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The background is the low intention of entrepreneurship in Siliwangi University Economic Education students. With the aim of knowing the effect of Entrepreneurship Education and Self-Efficacy on the Intention of Entrepreneurial Students of the Siliwangi University Economic Education class of 2015-2018. The explanatory survey method was used to complete the study, with the population of all students of the Siliwangi University Economic Education class of 2015-2018 totaling 503 students. While the sample technique used was random sampling by taking 223 students representing each class. Data obtained through observation, interviews, and questionnaires and analyzed using multiple linear regression with the help of IBM SPSS v.23 for Windows. The results showed that entrepreneurship education had a positive and significant effect on entrepreneurial intentions by 17.9% and obtained t_count> t_table (2.215> 1.6518), sig t = 0.028 <α = 0.05. Continued Self-efficacy has a positive and significant effect on entrepreneurial intentions of 61.1% and obtained t_ (count)> t table (15.1969> 1.6518), sig t = 0.000 <α = 0.05. Entrepreneurship education and self-efficacy were simultaneously obtained positive and significant effect on entrepreneurial intention of 61.8% and obtained F_count> F table (180.433> 3.0368), Sig F = 0,000 <α = 0.05.Keyword: Entrepreneurship, Intention, Students